Citizens’ Behavior as a Driver of Energy Transition and Greening of the Economy in the Russian Arctic: Findings of a Sociological Survey in the Murmansk Region and Karelia - Sergey Tishkov; Arsen Tleppayev; Valentina Karginova-Gubinova; Alexander Volkov; Anton Shcherbak (Applied Sciences, 2022)
Due to the depletion of traditional energy sources, the rising costs of their operation and the need to transition to a sustainable economy, it becomes relevant to increase the share of renewable energy sources in total consumption. The purpose of this study is to determine the role of renewable energy and the establishment of factors determining pro-environmental behavior. The data of the author’s sociological survey of the population of the Arctic regions of Russia and methods of descriptive statistics were used, and regression analysis was carried out. The study shows the ecological and energy characteristics of the Arctic regions of Russia. The main advantages and possibilities of transition to renewable energy sources have been identified. A relationship has been established between the degree of involvement in pro-environmental behavior and knowledge about renewable energy, the perceived importance of environmental problems, age, income, education, amount of waste produced and current electricity costs. It is shown that the degree of involvement in pro-environmental behavior affects the willingness to pay more for renewable energy. A number of institutional measures to promote renewable energy, increase willingness to pay for renewable energy and spread pro-environmental behavior are proposed.